Effects of mulch films with different thicknesses on the microbial community of tobacco rhizosphere soil in Yunnan laterite - Wang, Shuaibing; Li, Qiuping; Ye, Changbing; Ma, Wenqing; Sun, Yandong; Zhao, Bin; Zeng, Weiqing; Yue, Zhiqiang; Li, Lan; Li, Dandan (Frontiers in Microbiology, 2024)
The mulch film (MF) management model of agricultural field affects the physical and chemical properties of soil (PCPS) and the microorganism community structure; however, studies on the relationship between the rhizosphere microorganism community structure and the thickness of MF are still poor. To understand the interactions among MF thickness, PCPS, and rhizosphere microorganism, a study was conducted by using integrated metagenomic strategy in tobacco rhizosphere soil treated with four commonly representative used thicknesses of MFs (0.004mm, 0.006mm, 0.008mm, 0.010mm) in Yunnan laterite. The results showed that agronomic traits such as tobacco plant height (TPH), leaf number (LN), fresh leaf weight (FLW), and dry leaf weight (DLW) were significantly (p < 0.01) improved in the filed mulched with the thickest film (0.010mm) compared with the exposed field (CK), therer were 6.81% and 5.54% increase in FLW and TPH separately. And correlation analyses revealed a significant positive correlation of MF thickness with soil water content (SWC), soil organic matter (SOM), total nitrogen (TN), available nitrogen (AN), total phosphorus (TP), and available phosphorus (AP) (all p < 0.01), while MF thickness was negatively correlated with soil temperature (ST) (p < 0.01).In addition, the community structure of rhizosphere soil bacteria was been significantly changed overall by the MF thickness, which also interfered with the function of rhizosphere soil bacteria. The correlation analyses showed that the abundance of Bradyrhizobium and Nitrospira were positively correlated with the MF thickness, while that of sphinsinomonas and Massilia were negatively correlated with it. This indicates that with the increase of MF thickness, the ability of rhizosphere soil to utilize N and remove harmful molecules was strengthened, while the capacity of the rhizosphere soil to degrade pollutants was greatly reduced. These findings provide additional insights into the potential risks of the application of different thickness MF, particularly concerning PCPS and soil microbial communities.